Addition of Prucalopride to Standard Bowel Preparation Does Not Improve Colonic Mucosa Visualization—A Retrospective Observational Cohort Study - Singh, Gaurav Kr; Chauhan, Shamshersingh G.; Lad, Saiprasad S.; Sethiya, Pratik R.; Gattani, Mayur G.; Walke, Swapnil; Shah, Mit; Pandey, Vikas R.; Ingle, Meghraj A. (Journal of Digestive Endoscopy, 2022)
Background Colonoscopy is currently gold standard for visualizing colonic mucosa. Presence of constipation is generally associated with poor bowel preparation. We compared effect on colonic cleansing when prucalopride was used as adjunct with polyethylene glycol (PEG) in patients of constipation.Methods A retrospective study was conducted at our center. One 70 patients with constipation were enrolled in two groups of who took only PEG and other of prucalopride plus PEG+ for bowel preparation. They underwent colonoscopy by a single-blinded experienced endoscopist. Bowel preparation quality was reported by Boston bowel preparation scale prior to washing or suctioning. The groups were analyzed for bowel preparation quality and side effects in either groups based on preformed questionnaire.Results Mean Boston Stool preparation Score (BSS) in PEG group (5.33 ± 1.43) was slightly higher than PEG+ (5.16 + 1.37) (p-value =0.44). The total number of patients with side effects was higher in PEG+ group than PEG group. (p < 0.05).Conclusion We conclude addition of prucalopride has no additional benefit when added with standard bowel preparation in patients of constipation. It may rather lead to noncompliance and inferior bowel preparation due to increased side effects.
Keywords: Boston stool preparation score; bowel preparation; colonoscopy; constipation; polyethylene glycol; prucalopride